Rapid degradation of refractory organic pollutants by continuous ozonation in a micro-packed bed reactor. (May 2021) - Cao, Qiang; Sang, Le; Tu, Jiacheng; Xiao, Yushi; Liu, Na; Wu, Lidong; Zhang, Jisong
Abstract: Recently microreactor technology attracts attention due to the excellent multiphase mixing and enhanced mass transfer. Herein, a continuous ozonation system based on a micro-packed bed reactor (μPBR) was used to improve the dissolution rate of ozone and achieved a rapid and efficient degradation of refractory organic pollutants. The effects of liquid flow rate, gas flow rate, initial pH, initial O3 concentration and initial phenol concentration on the phenol and chemical oxygen demand (COD) removal efficiencies were also investigated. Experimental results showed that phenol and COD removal efficiencies under optimal conditions achieved 100.0% and 86.4%, respectively. Compared with large-scale reactors, the apparent reaction rate constant in μPBR increased by 1-2 orders of magnitude. In addition, some typical organic pollutants (including phenols, antibiotics and dyes) were treated by ozonation in μPBR. The removal efficiencies of these organic pollutants and COD achieved 100.0% and 70.2%–80.5% within 71 s, respectively. In this continuous treatment system, 100% of the unreacted ozone was converted to oxygen, which promoted the healthy development of aquatic ecosystems. Thus, this continuous system based on μPBR is a promising method in rapid and efficient treating refractory organic pollutants. Graphical abstract: Image 1 Highlights: A continuous ozonation system based on a μPBR was developed for rapid degradation of refractory organic pollutants. Compared with large-scale reactors, the apparent degradation rate constant was increased by 1-2 orders of magnitude. The removal efficiency of pollutants and COD in μPBR achieved 100% and 70%–80% within 71 s, respectively. Higher removal efficiency of pollutants and COD were attributed to the higher gas-liquid mass transfer in μPBR.